Binary Mixtures with Deep Eutectic Solvents: Comparing Properties with a Non–Ideality Approach - Caroli-Rezende, M (Elsevier B.V., 2022)
The non–ideality approach for the comparison of different properties of related binary mixtures of deep eutectic solvents (DESs) is illustrated with seventy examples from the literature. A preferential–solvation index (PSI) is used to compare polarities and the preferential solvation of solvatochromic probes in these systems. A non–ideality index (NII) and/or area (NIA) allow the comparison of thermodynamic properties of related mixtures. The approach, which is of easy application from experimental plots, can in principle be used for the comparison of any property of related binary mixtures of DESs. It is not based on theoretical assumptions and complements existing models, by comparing scattered data from different sources and revealing unexpected trends or patterns with a predictive power. It thus represents a simple alternative to the problem of interpreting and predicting the behavior of such complex, multi-component mixtures, which defy the application of theoretical models to their rationalization. © 2022 Elsevier B.V.